Pembelajaran Pendidikan Jasmani dan Olahraga berbasis Blended Learning di Sekolah Menengah Pertama - Andif Victoria; Pinton Setya Mustafa; Dedi Ardiyanto (Peneliti.net, 2021)
The development of technology and information is so rapid in the world of education and learning. As a result, changes in learning patterns continue to develop dynamically. The purpose of this article is to discuss physical education and sports based on blended learning at the junior high school. This research is a literature study with a qualitative approach, which examines references related to the topic of physical education and blended learning. The findings of this study describe that blended learning is a learning process that utilizes various media and technologies. Learning takes place conventionally (face to face), self learning, and online learning. The importance of mixed learning is justified by the fact that learning sports a communication activity can be realized both in the classroom and outside the classroom. Blended learning-based learning provides a number of important advantages for teachers and students, including helping educators to develop better in the learning process according to learning styles and preferences in learning, providing realistic practical opportunities for teachers and educators to learn independently, be useful, and continue to develop active learners in the learning process responsible for their own work. Blended learning based learning can be presented through several online programs.